Pengembangan Moderasi dan Pluralisme Di Tengah Arus Globalisasi - Ulik Arlina; Sokip Sokip; Asrop Syafi’i (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aims to describe the development of moderation and pluralism in the midst of globalization. This type of research is qualitative with a descriptive-analysis approach and literature study (library research). The main sources in this research are books, articles and other reading sources related to the theme of developing moderation and pluralism amidst globalization. The results of this research are 1) Moderation is a person's attitude that does not side with the extreme right and extreme left. This attitude is in the middle and does not side with either one. This is as stated in an expression, khairul age ausathuha (the best thing is the middle), 2) Indicators of religious moderation include national commitment, tolerance, non-violence and accommodating local culture, 3) Internalization of religious moderation in higher education by means of : a) The existence of indicators of religious moderation, b) Support from all higher education academics, c) The role of lecturers, d) Seminars and the existence of a house for religious moderation. Challenges to religious moderation in Indonesia include: a) Radicalism and extremism b) Limited understanding of religion c) The influence of globalization and d) Religious education that is not yet comprehensive. Pluralism is a philosophical view that does not reduce everything to one final principle, but accepts diversity. Pluralism concerns the religious, cultural and political fields.